The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.652033
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phytochemicals in Bladder Cancer Prevention and Therapy

Abstract: Phytochemicals are natural small-molecule compounds derived from plants that have attracted attention for their anticancer activities. Some phytochemicals have been developed as first-line anticancer drugs, such as paclitaxel and vincristine. In addition, several phytochemicals show good tumor suppression functions in various cancer types. Bladder cancer is a malignant tumor of the urinary system. To date, few specific phytochemicals have been used for bladder cancer therapy, although many have been studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 122 publications
(134 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, other studies showed the anticancer effect of LEO, while anticancer activity could not be attributed to its single constituents [ 158 , 159 ]. The anticancer activities of plant essential oils have been usually used as a paragon to compare essential oils from different sources.…”
Section: Leo Therapeuticsmentioning
confidence: 99%
“…Furthermore, other studies showed the anticancer effect of LEO, while anticancer activity could not be attributed to its single constituents [ 158 , 159 ]. The anticancer activities of plant essential oils have been usually used as a paragon to compare essential oils from different sources.…”
Section: Leo Therapeuticsmentioning
confidence: 99%
“…BLCA can be divided into muscle-invasive BLCA (MIBC) and non-muscle invasive BLCA (NMIBC). However, given the high mortality and progression of MIBC and the high recurrence rate of NMIBC, bladder cancer remains a difficult problem worldwide (3,4). The value of bacillus Calmette Guerin (BCG) against immunotherapy in NMIBC is widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to discover new agents that are effective and safe with fewer side effects that can selectively suppress the growth of bladder cancer cells. In this respect, natural phytochemicals are coming into the spotlight due to their low cost, low toxicity, and low hostility in bladder cancer prevention and therapy (Xia et al 2021). Recently, several medical plants and phytochemicals, including Radix Sophorae Flavescentis, Daphne genkwa, Tripterygium wilfordii, and flavonoids, steroids, alkaloids and quinone compounds from these natural plants have been reported to have anti-bladder cancer effect through apoptosis inducing (Jo et al 2020;Xia et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, natural phytochemicals are coming into the spotlight due to their low cost, low toxicity, and low hostility in bladder cancer prevention and therapy (Xia et al 2021). Recently, several medical plants and phytochemicals, including Radix Sophorae Flavescentis, Daphne genkwa, Tripterygium wilfordii, and flavonoids, steroids, alkaloids and quinone compounds from these natural plants have been reported to have anti-bladder cancer effect through apoptosis inducing (Jo et al 2020;Xia et al 2021). Apoptosis, also known as programmed cell death, is a precisely and essential regulated mechanism for regulating cell and tissue homeostasis and organism function in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation